Evaluating Thermal Insulation Strategies for High-Rise Residential Buildings in Sarajevo - Florian Teichmann; Azra Korjenic; Lamija Balić; Mirela Idrizović; Aldin Turković; Amir Ljubijankić; Venera Simonović; Sanela Klarić (Energies)
Aging residential buildings in urban areas require effective thermal insulation to enhance energy efficiency and indoor comfort. In Bosnia and Herzegovina (BiH), expanded polystyrene (EPS) is the most commonly used insulation material due to its affordability, despite concerns regarding its flammability and environmental impact. While regulatory changes since 2019 have recommended rock wool for high-rise buildings, the absence of binding fire safety regulations has allowed the continued use of EPS, often driven by financial constraints. This study examines energy efficiency refurbishments in Sarajevo’s high-rise residential buildings and analyze the implications of the partial implementation of recommended measures. Using case studies, surveys, and expert interviews, this research identifies key challenges, such as limited funding, fragmented renovations, and inconsistent coordination between stakeholders. The findings indicate that facade insulation is often prioritized over comprehensive upgrades, including window replacement and heating system improvements, leading to suboptimal energy savings and minimal cost reductions for residents. Additionally, the complexity of multi-apartment ownership structures hinders uniform improvements in energy efficiency. Despite these challenges, property values tend to increase after renovation, highlighting the long-term financial benefits. To maximize energy savings and ensure sustainable urban housing, stronger interdisciplinary collaboration, improved funding mechanisms, and adherence to fire-safety standards are necessary. These measures would enhance the effectiveness of renovations and support long-term energy efficiency strategies.